The calculation of desalination of mineralized porous ice at thawing - A. V. Sosnovsky; I. I. Kontorovich (Лëд и снег)
The results obtained in this work demonstrate that dynamics of desalination of porous ice depends on a mobility of ions of salts, and the mobility is determined by the diffusion coefficient. The ice was made by freezing of mineralized water of different chemical composition. Model calculations of average mineralization of the porous ice at its thawing were made, and the ion concentrations of different salts were defined. Values of the diffusion coefficients of the salt ions in the film of brine ice pellets were obtained by means of comparison of results of measurements and calculations of dynamics of content of the salt ions in a porous ice at its thawing. The diffusion coefficient of ions Na+, Cl−, SO4 2− is by order of magnitude larger than that of Ca2+ and by two orders of magnitudethan HCO3 −. This results in that the content of ions Na+, Cl−, SO42− decreases in porous ice at its thawing 3 times faster than the content of the ions Ca2+. Basing on analysis of chemical composition of drainage water in some regions in Russia a possibility to desalinate the porous ice formed during the winter sprinkling is demonstrated.